WRITTEN GAMBLING DISCOURSE IN SPANISH - Bobchynets , Lyubov (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The aim of our studies is to suggest the definition of gambling discourse, to define its types and to describe lexico-grammar, sintactic and graphic peculiarities of the texts included in gambling discourse. The studied discourse belongs to institutional and ritual discourse because gambling games possess rules which the gamblers should follow obligatorily. Gambling discourse is represented by oral and written form. We determine various types of texts belonging to the gambling discourse: advertising texts in the sphere of gambling; specialized texts of gambling discourse; texts of gamblers’ communication during the game and outside the game. Among lexical resources of gambling discourse we single out gambling terms, words of positive evaluation, metaphors, metonymy, hyperbole, comparison. Grammar and syntactic resorces include nominative and imperative sentences, rhetoric questions which communicate a dialogue character to written gambling discourse and motivate potential gamblers to play. Graphic means are characterized by the use of symbols, numbers, verbal and non verbal resources, such as change of colors and sizes, capitalization, animation, outlined text, links to other web pages dedicated to gambling. The range of lexical, grammar, syntactical and graphic means represent a positive image of a game and incent the gamblers to play. The texts of gambling discourse perform nominative, informative and expressive functions._____________References:• Bobchynets, L. I. Reklamni teksty dyskursu azartnykh igor u suchasnii ispanskii movi. [Advertising texts of gambling discourse in Contemporary Spanish] Visnyk Cherkaskoho universytetu. Seriia: Filologichni nauky [Cherkasy University Messenger. Series: Philological Sciences] 27 (360) (2015): 22–27 (in Ukr.).• Koliesnikova, I. A. Deiaki aspekty spetsyfiky arkhitektoniky profesiinoho dyskursu [Some aspects of the architectonics of a professional discourse] Studia Linguistica4 (2010): 428–432 (in Ukr.).• Ushchyna, V. A. Pozytsionuvannia subiekta v anglomovnomu dyskursi ryzyku: sotsiokognityvnyi aspekt [Positioning of a subject in English discourse of risk: sociocognitive aspect] (Lutsk: Vezha-Druk., 2015), 380 (in Ukr.).• Alarcón, M. A. Aproximaciones al concepto de Discurso Profesional Docente. Literatura y Lingüística23 (2011): 123–140, Santiago de Chile.• Pérez Latorre, Ó. El significado en juego: sobre la dimensión lúdica del discurso del videojuego. Proceedings of the 10th World Congress of the International Association for Semiotic Studies (IASS/AIS) Universidade da Coruña (España / Spain) (2012): 1901–1910.• Van Dijk,  El discurso como estructura y proceso. Estudio sobre el discurso (Barcelona: Editorial Gedisa, 2000).Illustrative materialпа:• Botín, Todos los juegos de cartas (Barcelona: Robinbook, 2011).• Como hacer trampas en los juegos de cartas, http://es.wikihow.com/hacer-trampa-en-los-juegos-de-cartas (accessed 12.04.2021).• Cristales para ver las cartas de tu rival, http://es.pokernews.com/noticias/2013/06/cristales-para-ver-las-cartas-de-tu-rival-9823.htm (accessed06.2021).• El juego del mus. Todas sus reglas y señas (Madrid: Tikal Ediciones, 2013).• Foro de póker, http://es.pokernews.com/foro-de-póquer/topic535/ (accessed 26.07.2022).• Guía del juego para los amantes del casino, http://www.acanomas.com/Guia-del-Juego-para-los-Amantes-del-Casino/1505/Glosario.htm (accessed 15.05.2022).• Loterías y apuestas, http://www.loteriasyapuestas.es (accessed 16.05.2022).• Marín Bellón,  Dos turcos detenidos en Argentina por marcar las cartas, http://abcblogs.abc.es/poker-ajedrez/public/post/dos-turcos-detenidos-en-argentina-por-marcar-las-cartas-11299.asp/ (accessed 16.05.2022).• Reglas de juegos, http://www.magnojuegos.com/juegosonline/escobadel15/reglas (accessed 17.05.2022).• Torneo latinoamericano de póker por equipos, http://www.pokergratis.es/torneo-latinoamericano-de-poker-por-equipos (accessed 17.05.2022).
Keywords: gambling discourse, professional discourse, ludic discourse, advertising texts